Low temperature structural stability of Fe90Sc10 nanoglasses. Issue 3 (4th March 2018) - Wang, Chaomin; Feng, Tao; Wang, Di; Mu, Xiaoke; Ghafari, Mohammad; Witte, Ralf; Kobler, Aaron; Kübel, Christian; Ivanisenko, Yulia; Gleiter, Herbert; Hahn, Horst
ABSTRACT: The structural stability of Fe90 Sc10 nanoglasses has been studied by means of low temperature crystallization. Specimens were annealed in situ in a transmission electron microscope, and ex situ in an ultra-high vacuum tube-furnace. Both studies led to similar results. The structure of the Fe90 Sc10 nanoglasses was stable for up to 2 h when annealed at 150°C. Annealing the Fe90 Sc10 nanoglasses at higher temperature resulted in the formation of the nanocrystalline bcc-Fe(Sc). Impact statement The structural evolution of Fe90 Sc10 nanoglasses has been studied in detail during low temperature annealing. Our results indicate that the nanostructure of Fe90 Sc10 nanoglasses is quite stable at low temperature. GRAPHICAL ABSTRACT: